The later prehistory of ’black holes’: regionality and the south-west Scottish Iron Age - Cavers, Graeme (Proceedings of the Society of Antiquaries of Scotland, 2009)
The Iron Age archaeology of south-west Scotland has always been anonymous in national syntheses of the period in comparison to better studied areas. This lack of attention does not reflect the quality of the archaeological record however, which testifies to a rich and diverse later prehistoric society. This paper is a discussion of the range and nature of the evidence for Iron Age society in Dumfries and Galloway west of the Nith, considering affinities with other areas, particularly the Atlantic regions to the north, and exploring the reasons for the form and distribution of Iron Age monuments in the area. It is argued that a reanalysis of our definition and interpretation of fundamental characteristics of later prehistoric society, such as domestic monumentality, may be rewarding in heterogeneous and unsorted areas such as Galloway. *This paper was awarded the RBK Stevenson Award